PORTRAIT OF ZAKAT MANAGEMENT AT SOME ZAKAT INSTITUTIONS IN MAKASSAR CITY - Asmira, Sri; Basri, Muh. Arfah; Muin, Rahmawati; Lutfi, Mukhtar (ISAFIR: Islamic Accounting and Finance Review, 2023)
The purpose of writing this article is to analyze the form of zakat management at BAZNAS Makassar City and several LAZs in Makassar City such as Dhompet Dhuafa, LAZISMU, Wahdah Islamiyah, Yatim Mandiri, and Rumah Zakat Makassar City. This research is a qualitative research using descriptive analysis techniques with library research. The results of the study show that zakat management is carried out by BAZNAS and several LAZs in Makassar City, namely they collect zakat in various ways that can make it easier for muzakki to pay their zakat. Then in the zakat distribution and utilization program, they focus on the same issues as in the religious, economic, educational, health and social fields. Basically, BAZ and LAZ manage zakat with the same goal, namely to eradicate poverty and encourage the people's economy. The obstacles faced in the management of zakat are inseparable from the problem of the lack of available zakat funds, the lack of public knowledge and trust regarding the management of zakat by zakat institutions, and the lack of adequate human resources in managing zakat. The implication of this research is that various zakat management programs need to be developed in a better, more productive and modern direction. So as to increase efficiency and effectiveness in the management of zakat at zakat institutions in general.